2014
DOI: 10.5713/ajas.2013.13654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Housing Systems and the Diet Supplements on the Slaughter Value and Concentration of Mineral Elements in the Loin Muscle of Lambs

Abstract: The objective of this study was to investigate the effect of maintenance system as well as the effect of Se, Zn, and vitamin E supplementation of ram-lambs on the slaughter value and concentration of mineral elements in the loin muscle of lambs. The experiment was conducted on 72 Polish Merino ram-lambs divided into three groups: group C, indoor with no supplement, 19 lambs; S, indoor with supplement, 23 lambs; G, outdoor with no supplement, 30 lambs. From birth all the lambs were maintained indoor with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Electronic scales and tapelines were used to measure the slaughter performance metrics after 6 months of age, including body weight, body size, and carcass yield. Carcass percentage, dressing percentage, net meat percentage, and loin eye area were recorded in accordance with previously reported studies [17,18]. The meat quality was evaluated by shear force, pH, color chroma, and the muscle marbling grade of the longissimus dorsi tissue, in accordance with previously reported studies [2,19].…”
Section: Sample Preparation Collection and Measures Of Production Psupporting
confidence: 79%
“…Electronic scales and tapelines were used to measure the slaughter performance metrics after 6 months of age, including body weight, body size, and carcass yield. Carcass percentage, dressing percentage, net meat percentage, and loin eye area were recorded in accordance with previously reported studies [17,18]. The meat quality was evaluated by shear force, pH, color chroma, and the muscle marbling grade of the longissimus dorsi tissue, in accordance with previously reported studies [2,19].…”
Section: Sample Preparation Collection and Measures Of Production Psupporting
confidence: 79%
“…Some studies on grazing lambs (Dixit et al 2001;Benyi et al 2006) in semi-intensive systems (González et al 2002) have found that lambs fattened in seasons which high ambient temperatures showed reduced feed intake, compared to other seasons. The differences between feeding lambs at the indoor system (with concentrate) and grazing lambs suggest that the diet composition has a greater influence on lamb performance than the environmental conditions do (Gabryszuk et al 2014), however, in the present study, lambs received the same diet (concentrate and pasture). In temperate regions especially in winter ewes prefer pens with straw bedding than wooden slats (Gordon & Cockram, 1995).…”
Section: Resultsmentioning
confidence: 40%
“…An electronic scale and a tape measure were used to measure the slaughter performance indicators at 6 months of age, including body weight, body size, and carcass output. We referred to previous studies [ 15 , 16 ] to determine the carcass percentage, slaughter percentage, net meat percentage, and eye muscle area. The quality of the meat was evaluated by shear force, pH, color, and muscle marbling of the longissimus dorsi tissue [ 17 ].…”
Section: Methodsmentioning
confidence: 99%